The impact of precompetition state on athletic performance among track and field athletes using machine learning - Zhang, Y.; Fu, P.; Yu, Q.; Niu, Q.; Nie, D.; Dou, X.; Zhang, X. (Frontiers in Physiology, 2025)
Objective: This study aims to compare the differences in the precompetition status (nutritional, physiological, biochemical, psychological, and sleep statuses) among college track and field athletes with different competition performances and to screen for key indicators of differences affecting athletic performance.